The Effect of Platelet-rich Fibrin Matrix on Rotator Cuff Healing in a Rat Model - Hasan, S.; Weinberg, M.; Khatib, O.; Jazrawi, L.; Strauss, E. J. (International Journal of Sports Medicine, 2016)
The purpose of the current study was to determine if the application of platelet-rich fibrin matrix could improve regeneration of the tendon-bone insertion site in a rat rotator cuff repair model. 25 Lewis syngeneic rats underwent bilateral tenotomy and repair of the supraspinatus tendon. 10 separate rats were used for PRFM harvest. All left (control) shoulders underwent transosseous rotator cuff repair, while all right (treatment) shoulders were repaired similarly with PRFM augmentation. 9 rats were sacrificed at 2-weeks and ten at 4-weeks for biomechanical testing. 3 separate rats were sacrificed at 2-weeks and 4-weeks each for histologic analysis of the insertion site. At 2 weeks, the experimental group repairs were significantly stronger in ultimate load to failure (P=0.01), stress (P=0.03), and stiffness (P=0.03). Differences in biomechanical testing were not found between the groups at 4 weeks. Histological analysis revealed less collagen organization and cartilage formation at the insertion site in the experimental group. Semiquantitative histologic analysis confirmed our qualitative assessment of the specimens. PRFM does not recapitulate the native enthesis, but rather induces an exuberant and disordered healing response that is characterized by fibrovascular scar tissue.
Keywords: platelet-rich plasma; rotator cuff; shoulder; rat; sports medicine